Business Plan for Designing a Franchise Model for 'Madurai Idly Shop' - JAYAKUMAR, GAUTHAM KUMAR (2015)
Madurai Idly Shop(MIS) is a Ethnic Quick Service Restaurant Chain in Bangalore, India. The business plan is created for two objectives. Firstly, to understand the current capabilities of its existing business. Secondly, to design a franchise model for MIS.